New insights on large-scale structures at the Forsmark site, Central Sweden - Reprocessing of high-resolution seismic data - Brojerdi, F.; Juhlin, Christopher; Malehmir, A.; Lundberg, E. (European Association of Geoscientists and Engineers, EAGE, 2012)
We present reprocessed data from seven profiles from the Forsmark site, the location where Sweden will store its spent nuclear fuel. The reprocessed data show improved images of the crust below 1 km since lower frequencies were preserved in the new processing sequences. These sections together with data from a longer more regional profile to the south of the area indicate that there may be a previously unidentified larger southwesterly dipping deformation or fracture zone in the southern part of the Forsmark area, well away from the planned repository.